Genetic analysis of influenza B viruses isolated in Uganda during the 2009–2010 seasons - Byarugaba, Denis K (BioMed Central, 2013)
BACKGROUND: Influenza B viruses can cause morbidity and mortality in humans but due to the lack of an animal reservoir are not associated with pandemics. Because of this, there is relatively limited genetic sequences available for influenza B viruses, especially from developing countries. Complete genome analysis of one influenza B virus and several gene segments of other influenza B viruses isolated from Uganda from May 2009 through December 2010 was therefore undertaken in this study. METHODS: Samples were collected from patients showing influenza like illness and screened for influenza A and B by PCR. Influenza B viruses were isolated on Madin-Darby Canine Kidney cells and selected isolates were subsequently sequenced and analyzed phylogenetically. FINDINGS: Of the 2,089 samples collected during the period, 292 were positive by PCR for influenza A or B; 12.3% of the PCR positives were influenza B. Thirty influenza B viruses were recovered and of these 25 that grew well consistently on subculture were subjected to further analysis. All the isolates belonged to the B/Victoria-lineage as identified by hemagglutination inhibition assay and genetic analysis except one isolate that grouped with the B-Yamagata-lineage. The Ugandan B/Victoria-lineage isolates grouped in clade 1 which was defined by the N75K, N165K and S172P substitutions in hemagglutinin (HA) protein clustered together with the B/Brisbane/60/2008 vaccine strain. The Yamagata-like Ugandan strain, B/Uganda/MUWRP-053/2009, clustered with clade 3 Yamagata viruses such as B/Bangladesh/3333/2007 which is characterized by S150I and N166Y substitutions in HA. CONCLUSION: In general there was limited variation among the Ugandan isolates but they were interestingly closer to viruses from West and North Africa than from neighboring Kenya. Our isolates closely matched the World Health Organization recommended vaccines for the seasons.